THE RELATIONSHIP BETWEEN AIR FREIGHT, TRADE OPENNESS, INDUSTRIAL DEVELOPMENT AND ECONOMIC DEVELOPMENT FOR SINGAPORE: A CO-INTEGRATED REGRESSION APPROACH (Third Sector Social Economic Review, 2023)
The main purpose of this article is to examine the relationship between airline transport, trade openness, industrial development and economic development from 1970 to 2020 by using multiple regression, Phillips-Ouliaris cointegration test and fully modified least squares method for Singapore. First of all, the effects of air transport, trade openness and industrial development on economic growth is measured by employing the multivariate regression model. In this context, the results obtained for Singapore between 1970 and 2020 have been empirically determined that only air transport triggers economic development as an independent variable. In addition, according to the results of the Phillips-Ouliaris cointegration test and fully modified least squares method for Singapore between 1970 and 2020, there is a long-term relationship between air transport, trade openness, industrial development and economic development. In light of these findings, trade liberalization policies must be flexible and adaptable to build the more robust global tourism infrastructure necessary for economic growth and healthy transportation around the world. As a result, strategic steps should be taken through appropriate policy tools to expand international air transport infrastructure to benefit people and their lives. It is important to identify market imperfections that may hinder success in securing sufficient numbers of air transport to facilitate economic development. Moreover, while the conceptual model for Singapore reflects static relationships, the competitive, responsive and dynamic nature of the aviation market should be regulated by structural reforms by policy makers.
Keywords: Air Freight; Trade Openness; Industrial Development; Economic Development; Multiple Regression